Large-scale assessment of polyglutamine repeat expansions in Parkinson disease. (13th October 2015) - Wang, Lisa; Aasly, Jan O.; Annesi, Grazia; Bardien, Soraya; Bozi, Maria; Brice, Alexis; Carr, Jonathan; Chung, Sun J.; Clarke, Carl; Crosiers, David; Deutschländer, Angela; Eckstein, Gertrud; et al.
Abstract : Objectives: We aim to clarify the pathogenic role of intermediate size repeat expansions of SCA2, SCA3, SCA6, and SCA17 as risk factors for idiopathic Parkinson disease (PD). Methods: We invited researchers from the Genetic Epidemiology of Parkinson's Disease Consortium to participate in the study. There were 12, 346 cases and 8, 164 controls genotyped, for a total of 4 repeats within the SCA2, SCA3, SCA6, and SCA17 genes. Fixed- and random-effects models were used to estimate the summary risk estimates for the genes. We investigated between-study heterogeneity and heterogeneity between different ethnic populations. Results: We did not observe any definite pathogenic repeat expansions for SCA2, SCA3, SCA6, and SCA17 genes in patients with idiopathic PD from Caucasian and Asian populations. Furthermore, overall analysis did not reveal any significant association between intermediate repeats and PD. The effect estimates (odds ratio) ranged from 0.93 to 1.01 in the overall cohort for the SCA2, SCA3, SCA6, and SCA17 loci. Conclusions: Our study did not support a major role for definite pathogenic repeat expansions in SCA2, SCA3, SCA6, and SCA17 genes for idiopathic PD. Thus, results of this large study do not support diagnostic screening of SCA2, SCA3, SCA6, and SCA17 gene repeats in the common idiopathic form of PD. Likewise, this largest multicentered study performed to date excludes the role of intermediate repeats of these genes as a risk factor for PD.